Risorgimento in exile Italian emigres and the liberal international in the post-Napoleonic era - Isabella, Maurizio (Oxford University Press, 2009)
The experience of exiles was fundamental for shaping Italian national identity. 'Risorgimento in Exile' investigates the contribution to Italian nationalism made by the numerous patriots who were forced to live in exile following failed revolutions in the Italian states.